2018
DOI: 10.1128/aem.01047-18
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Soluble Fiber Diet during Pregnancy Changes the Intestinal Microbiota, Improves Growth Performance, and Reduces Intestinal Permeability in Piglets

Abstract: Increasing evidence suggests that maternal diet during pregnancy modifies offspring's microbiota composition and intestinal development in a long-term manner. However, the effects of maternal soluble fiber diet during pregnancy on growth traits and the developing intestine are still underexplored. Sows were allocated to either control or 2.0% pregelatinized waxy maize starch plus guar gum (SF) dietary treatment during gestation. Growth performance, diarrhea incidence, gut microbiota composition and metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 54 publications
5
85
1
Order By: Relevance
“…Likewise, Shim et al (2005) also showed that dietary scFOS inclusion significantly increased butyric acid and isobutyric acid production of weaning piglets. SCFAs are important for intestinal health, as indicated by improved gut barrier function and accelerated intestinal growth in SCFAsinfused or fibre-treated piglets (Diao et al 2017;Cheng et al 2018). Acetic acid has been shown to be an anti-inflammatory substance to maintain intestinal homeostasis and butyric acid is considered to enhance intestinal barrier function by increasing the expression of tight junctions (Huang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Shim et al (2005) also showed that dietary scFOS inclusion significantly increased butyric acid and isobutyric acid production of weaning piglets. SCFAs are important for intestinal health, as indicated by improved gut barrier function and accelerated intestinal growth in SCFAsinfused or fibre-treated piglets (Diao et al 2017;Cheng et al 2018). Acetic acid has been shown to be an anti-inflammatory substance to maintain intestinal homeostasis and butyric acid is considered to enhance intestinal barrier function by increasing the expression of tight junctions (Huang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given the similarity in weaning day (d 28), diets and environment, we deduced that the difference may be due to the initial body weight (IBW) imparity. In the opinion of Cheng et al [31], maternal diet during pregnancy modifies microbiota and intestinal development of offspring in a long-term manner. In that way, different IBW may be closely associated with the microbiota and sow diet.…”
Section: Fecal Short Chain Fatty Acids Production and Serumal Indicesmentioning
confidence: 99%
“…Recent studies revealed that maternal diets and gut microbiota could directly affect the offspring development early in life [32, 33, 45]. For instance, sows treated with probiotic combinations resulted in improved microbiota diversity in neonatal piglets [46].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that lysozyme could be effective against a wide range of gastrointestinal pathogens, such as Listeria monocytogenes , Clostridium perfringens , Candida spp., and Helicobacter pylori in vitro [7, 21]. Reduced microbial diversity should result from combined factors including physiological preparation for parturition and lysozyme treatment [32, 46]. Furthermore, Spirochaetes , Euryarchaeota, and Actinobacteria significantly increased while Firmicutes showed a remarkable reduction in the 1.0 kg/t treated group compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation